2021
DOI: 10.1186/s12879-021-06459-z
|View full text |Cite
|
Sign up to set email alerts
|

HIV virological non-suppression and its associated factors in children on antiretroviral therapy at a major treatment centre in Southern Ghana: a cross-sectional study

Abstract: Background Children living with human immunodeficiency virus (HIV) infection require lifelong effective antiretroviral therapy (ART). The goal of ART in HIV-infected persons is sustained viral suppression. There is limited information on virological non-suppression or failure and its associated factors in children in resource limited countries, particularly Ghana. Methods A cross-sectional study of 250 children aged 8 months to 15 years who had bee… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
21
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 36 publications
4
21
4
Order By: Relevance
“…However, this study is not similar with the study conducted in Weliso town of Oromia, Ethiopia, Vietnam and Ghana in which adherence level had no statistically significant association [28][29][30]. The reason for the variation might be the difference in the method of data This study is similar with the study conducted in South Africa and Amhara regional hospitals in which CPT users were one of the independent predictors of virological failure or non suppressed viral among patients on follow up of first line ART treatment [31,32].…”
Section: Discussioncontrasting
confidence: 86%
“…However, this study is not similar with the study conducted in Weliso town of Oromia, Ethiopia, Vietnam and Ghana in which adherence level had no statistically significant association [28][29][30]. The reason for the variation might be the difference in the method of data This study is similar with the study conducted in South Africa and Amhara regional hospitals in which CPT users were one of the independent predictors of virological failure or non suppressed viral among patients on follow up of first line ART treatment [31,32].…”
Section: Discussioncontrasting
confidence: 86%
“…In subjects treated with nevirapine, the proportion of failure was much higher compared to those treated with efavirenz, but still comparable to findings of other studies reporting virological failure. 18,19 However, univariate analysis of first-line backbone regimens showed no statistically significant differences in hazard ratios.…”
Section: Discussionmentioning
confidence: 93%
“…9,15 Several factors that are known to increase the risk of virological failure on CLHIV include younger age at diagnosis or treatment initiation, WHO stage 3 and 4, lower CD4 count, nevirapine (NVP)-based regimen, and treatment interruption. 10,11,[16][17][18][19][20][21] This study aimed to determine the incidence of treatment failure with first-line ART in situations of limited VL monitoring in Indonesia, as well as to identify the predictors of treatment failure in order to assist clinicians in monitoring their patients more closely.…”
Section: H Uman Immunodeficiency Virus (Hiv)mentioning
confidence: 99%
“…Opportunistic infections, such as TB, have been shown to hamper VLS in children receiving ART [ 14 , 19 , 20 , 38 ]. Another study demonstrated that the initiation of ART in children reduces the incidence of TB [ 24 ].…”
Section: Discussionmentioning
confidence: 99%